Specific features of the situation in Kalinin and Kashin diocese prior to the start of Khruschev persecution (1954–1957) - Roman Tupikin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the peculiarities of church life in the Kalinin and Kashin diocese for three years before the start of Khrushchev’s “thaw”. Until 1954, taking into account the consequences of the persecution of the Russian Orthodox Church in the 1930s, a series of church and administrative transformations of the Kalinin diocese in the last years of the Great Patriotic War and the post-war period, determined by the needs of the Church, as well as the activities of diocesan bishops in 1935–1953, Church life in the Kalinin region was in decline. The revival of the Kalinin and Kashin diocese was initiated by Patriarch Alexy I (Simansky). By appointing as diocesan bishop an outstanding hierarch from the widowed clergy, who had an academic theological education and was imprisoned in the Solovetsky camp for special purposes, Bishop Barsanuphius (Grinevich), the patriarch, with the assistance of the Council for the Affairs of the Russian Orthodox Church, ensured non-interference in the activities of the bishop authorized by the Council for the Kalinin Region V.I. Hebronov, who was distinguished by his irreconcilable position towards the Church. In such conditions, Bishop Barsanuphius managed to achieve outstanding results in the revival of the diocese in three years: to increase the number of registered churches, to resume services in churches remote from Kalinin, where services had not been held for a long time, to increase the number of parish clergy, to stabilize the state of their morality, to ensure remote rural churches by clergy, to carry out repairs in them. Considering that the population of the Kalinin region was recognized as religious, the events of 1954–1957. were characterized by the patriarch, clergy, believers of the Kalinin region and even the authorized Hebronov as a revival.